2013
DOI: 10.1536/ihj.54.88
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Direct Renin Inhibitor, Aliskiren, in Patients With Resistant Hypertension

Abstract: SummaryCurrently there is no consensus regarding which add-on therapy to use in resistant hypertension. We have conducted an open observational study of the use of aliskiren in resistant hypertensive patients. Forty-three patients with resistant hypertension were included in the study. The inclusion criteria were as follows: 1) office blood pressure (BP) > 140/90 mmHg despite treatment with at least three or more antihypertensive drugs; 2) no prior therapy with aliskiren; and 3) no renal insufficiency. Follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The hypotensive effect of ALSK is potentiated when used in combination with diuretics or blockers of the RAAS. 22 Moreover, monotherapy with L-ARG was able to reduce but not normalize SBP, as observed in this study and in previous studies from our laboratory. 16 However, our most important finding is that the combination of these therapies significantly reduced the blood pressure of the hypertensive rats.…”
Section: Discussionsupporting
confidence: 86%
“…The hypotensive effect of ALSK is potentiated when used in combination with diuretics or blockers of the RAAS. 22 Moreover, monotherapy with L-ARG was able to reduce but not normalize SBP, as observed in this study and in previous studies from our laboratory. 16 However, our most important finding is that the combination of these therapies significantly reduced the blood pressure of the hypertensive rats.…”
Section: Discussionsupporting
confidence: 86%
“…7) A previous study has identified some predictors of inhospital mortality in acute type B aortic dissection including age, abrupt onset of chest pain, hypertension, kidney failure, pulse deficit, abnormal electrocardiography (ECG) findings, and absence of a nocturnal blood pressure fall. [8][9][10] Since patients with AAD usually receive medical treatment during the acute phase, Kudo, et al 11) suggest that maximum aortic diameter of ≥ 40 mm or ulcer-like projections at onset are predictors of aortic events. Actually, there is growing evidence that multiple assessments of several biomarkers may provide complementary information about the risk of death in aortic dissection patients.…”
mentioning
confidence: 99%
“…If the increases in aliskiren concentrations in the blood and antihypertensive effects are proportional, then that may explain the higher target BP achievement rate observed in the elderly patients. Trials of the antihypertensive effect and safety of aliskiren have been conducted in succession (19)(20)(21)(22)(23) following the ALTITUDE trial (13). The organ-protective effects of antihypertensive drugs are largely attributed to the decrease in BP, and aliskiren, which has a stable, 24-hour-long antihypertensive effect, appears to be useful for good BP management.…”
Section: Discussionmentioning
confidence: 99%